Thrombocytopaenia, Thromboxane And Prostacyclin Production During The Forssman Reaction In The Guinea-Pig: Effect Of A Thromboxane Synthetase Inhibitor - Westwick, J; Butler, K; Honey, A; Krishnamurthi, S; Kakkar, V V (Thrombosis and Haemostasis, 1981)
Intra venous (iv) injection of Forssman antibody into the guinea-pig (GP) is known to result in a rapid antigen antibody reaction in the lungs leading to bronchospasm and thrombocytopaenia. Death as a result of Forssman shock has been shown to be complement and platelet dependentGroups of 5 Duncan-Hartley GP (350-400g) received either 0.2ml (sub lethal groups) or 0.6ml (lethal groups) of rabbit anti Forssman antiserum (RAFA) iv, then 5ml blood samples were collected via carotid artery cannula, into 0.5ml ice cold EDTA (lOOmM) and indomethacin (180μM) mixture at 0, 1, 3 and 5 min. post injection. The blood samples were rapidly centrifuged at 15,000g for 3 min, plasma removed and frozen at -20°C until assayed. The plasma was then assayed for TxB2 and 6-oxo-PGF1α using specific RIA’s. There was a marked TxB2 production during the thrombocytopaenia with a concomitant small increase in 6-oxo-PGF1α production.However, when groups of 5 GPs were dosed iv with 0, 1, 3 or 10 mg/kg of UK-37, 248, a potent and selective thromboxane synthetase inhibitor, 3 mins prior to 0.2ml of RAFA the resulting thrombocytopaenia was not inhibited at 0, 0.5, 1, 2, 5, 10 and 15 min post RAFA. Thus thromboxane production does not appear to be contributory to the Forssman induced thrombocytopaenia in the GP.